Detection of Dengue Virus Transovarial Transmission in Dengue Hemorrhagic Fever Endemic Areas - Kasjono, Heru Subaris; Saepudin, Malik; Martini, Martini (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Dengue virus is a group of RNA viruses that are highly pathogenic in humans and spread quickly through the bites of Aedes aegypti and Aedes albopictus mosquitoes, especially in tropical countries. More than half a billion out of 100 countries worldwide are at serious risk of dengue virus infection. Vector surveillance activities with Ovitrap and detection of dengue virus types in Aedes aegypti and Aedes albopictus have never been carried out in Pontianak City. It is important in early alert systems at transmission foci. The purpose of this study was to prove the transovarial transmission of dengue virus in Aedes aegypti and Aedes albopictus mosquitoes with a transovarial transmission index (TTI) in endemic areas in Pontianak City, West Kalimantan. The method used in this research is descriptive observational, viral examination method with immunocytochemistry streptavidin-biotin peroxidase complex (ISBPC) and Polymerase Chain Reaction Transcription Reaction (PCR) aimed at proving the presence of transovarial transmission of dengue virus in the same period. The conclusion in this study is that there is evidence of transovarial transmission of dengue virus in Aedes mosquitoes in endemic areas by 29.3% in Sungai Jawi Dalam sub-district, West Pontianak sub-district, and 39.6% in Batu Layang sub-district, North Pontianak sub-district, mosquito density from the results of the Ovitrap Index measurement (OI) in Batu Layang Village is denser, namely 41.3%, compared to Sungai Jawi Village, which is 38.22% and has succeeded in identifying the type of dengue virus, namely the Dengue virus strain, in the two research locations.